Human Placental Mesenchymal Stem Cells-Exosomes Alleviate Endothelial Barrier Dysfunction via Cytoskeletal Remodeling through hsa-miR-148a-3p/ROCK1 Pathway - Yuzhen Lv; Wenqin Yu; Ruiui Xuan; Yulu Yang; Xiaolan Xue; Xiaowei Ma (Hindawi Limited, 2024)
Background. Endothelial barrier disruption of human pulmonary vascular endothelial cells (HPVECs) is an important pathogenic factor for acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Mesenchymal stem cells-exosome (MSCs-Exo) represents an ideal carrier for cell-free therapy. The therapeutic implication and underlying mechanism of human placental MSCs-Exo (HPMSCs-Exo) in ALI/ARDS need to be further explored. Materials and Methods. HPMSCs-Exo was extracted from HPMSCs and characterized. Then, the therapeutic effects of exosomes were evaluated in ALI mice and HPVECs. RNA-sequencing was applied to reveal the miRNA profile of HPMSCs-Exo and differentially expressed genes (DEGs) in HPMSCs-Exo-pretreated HPVECs. The targets of miRNAs were predicted by bioinformatics methods and correlated to DEGs. Finally, the role of hsa-miR-148a-3p/ROCK1 pathway in HPVECs has been further discussed. Results. The results showed that HPMSCs-Exo could downregulate Rho-associated coiled-coil-containing protein kinase 1 (ROCK1), upregulate the expression of zonula occludens-1 (ZO-1) and F-actin, promote HPVECs migration and tube formation, reduce cytoskeletal disorders and cell permeability, and thus improve ALI/ARDS. RNA-sequencing revealed the DEGs were mainly enriched in cell junction, angiogenesis, inflammation, and energy metabolism. HPMSCs-Exo contains multiple miRNAs which are associated with cytoskeletal function; the expression abundance of hsa-miR-148a-3p is the highest. Bioinformatic analysis identified ROCK1 as a target of hsa-miR-148a-3p. The overexpression of hsa-miR-148a-3p in HPMSCs-Exo promoted the migration and tube formation of HPVECs and reduced ROCK1 expression. However, the overexpression of ROCK1 on HPVECs reduced the therapeutic effect of HPMSCs-Exo. Conclusions. HPMSCs-Exo represents a protective regimen against endothelial barrier disruption of HPVECs in ALI/ARDS, and the hsa-miR-148a-3p/ROCK1 pathway plays an important role in this therapeutics implication.